1995
DOI: 10.1073/pnas.92.5.1744
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene transfer into hepatoma cells with lipopolyamine-condensed DNA particles presenting galactose ligands: a stage toward artificial viruses.

Abstract: Optimal in vitro gene delivery with cationic lipids requires an excess of cationic charges with respect to DNA phosphates. In these conditions, in vivo delivery will be hampered by interference from cationic lipid-binding macromolecules either circulating or in the extracellular matrix. To overcome this problem, we are developing a modular transfection system based on lipid-coated DNA particles reminiscent of enveloped viruses. The particle core consists of the lipopolyamine-condensed nucleic acid in an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(127 citation statements)
references
References 49 publications
6
117
1
2
Order By: Relevance
“…This toxic cellular response could be a consequence of the endo-lysosomal enzyme release into the cytoplasm as a result of excessive presence of membrane-disruptive PEI particles. 20 However, it seems that the transfection efficiency and toxicity of PEI correlated strongly with its molecular mass. For example, although less toxic, PEI (2 kDa) is some 2 orders of magnitude less efficient for gene delivery applications when compared with PEI (25 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…This toxic cellular response could be a consequence of the endo-lysosomal enzyme release into the cytoplasm as a result of excessive presence of membrane-disruptive PEI particles. 20 However, it seems that the transfection efficiency and toxicity of PEI correlated strongly with its molecular mass. For example, although less toxic, PEI (2 kDa) is some 2 orders of magnitude less efficient for gene delivery applications when compared with PEI (25 kDa).…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study reported enhancement of asialoglycoprotein receptor-mediated DNA transfer into human hepatoma HepG2 cells in the presence of the lipid lipofectam. 19 Enhanced transferrin-mediated gene transfer in the presence of the cationic lipid lipofectin in Hela cells has been reported. 20 Using [ 35 S]-labelled plasmid DNA the authors also showed enhanced intracellular DNA transfer by transferrin in the presence of lipofectin.…”
Section: Discussionmentioning
confidence: 99%
“…18 An additional study also showed enhancement of asialoglycoprotein receptor-mediated DNA transfer into human hepatoma HepG2 cells in the presence of the lipid lipofectam. 19 Hela cells transfected with the ligand transferrin also showed enhanced transfection with the liposome lipofectin. 20 We recently reported first results demonstrating enhancement of integrin-mediated gene delivery by addition of a liposome to melanoma, kidney and endothelial cell lines.…”
Section: Introductionmentioning
confidence: 96%
“…It is commonly thought that genomic DNA displaces the DNA condensing agents in the nucleus, thus releasing plasmid DNA and enabling gene expression. 231 However, Zabner et al 1 showed that even when lipoplexes were microinjected directly into the nucleus, gene expression was inhibited compared to naked DNA. It is likely that DNA release in the nucleus is dependent on the type of vector used, as Pollard et al 232 showed that PEI promoted nuclear delivery and DNA release in the nucleus, whereas cationic lipids did not.…”
Section: Postnuclear Eventsmentioning
confidence: 99%